Designing and explaining the strategic model for recognizing entrepreneurial opportunities in knowledge-based cooperative companies active in the agricultural sector - Afshin Bazi; Mojtaba Palouj; , Rasool Lavaei Adaryani; Ali Behrooz (تعاون و کشاورزی)
Context and purpose., The current research was conducted with the aim of identifying and prioritizing strategies for recognizing entrepreneurial opportunities in knowledge-based cooperative companies in the agricultural sector.Methodology/approach. In this research, the strengths, weaknesses, opportunities, and threats of recognizing entrepreneurial opportunities were identified based on theoretical foundations, and finally, using the opinion of 30 experts, it was monitored using the fuzzy Delphi method, and strategies for recognizing entrepreneurial opportunities were extracted. And after finalizing the strategies and giving them coefficient and weight with SPSS software, they were evaluated and ranked through the process of hierarchical analysis with the help of Expert Choice 11 software. At this stage, based on the Karjesi-Morgan table, 165 expert experts of knowledge-based cooperative companies active in the agricultural sector were selected as a statistical sample from among 281 companies.Findings and conclusions. Based on the SWOT analysis, the elements of the entrepreneurial opportunity recognition model were identified and after examining the twenty strategies, using the hierarchical analysis technique, the model elements were ranked and analyzed. The findings showed that agricultural knowledge-based businesses play a key role in creating and developing a knowledge-based economy, and economic growth and job creation are realized in accordance with the capacity of innovation and recognition of opportunities.Originality. This study presents the strategic model of recognizing entrepreneurial opportunities according to internal and external factors in knowledge-based cooperatives in the agricultural sector, which provides recognition of new opportunities and, subsequently, the improvement of knowledge-based management in the cooperative sector.